Diamond growth dynamics in a constrained system - Bai, Shengyuan; Díaz, Ramón D.; Muehle, Matthias; Garratt, Elias; Baryshev, Sergey V. (Frontiers in Carbon, 2024)
Single crystal diamond (SCD) is the most promising future semiconductor. At the same time, SCD has not been able to make much of an inroad into the microelectronics industry due to one major disadvantage that is the wafer size. Among a few contender technologies, epitaxial lateral outgrowth (ELO) using microwave plasma assisted chemical vapor deposition (MPACVD) has shown early promise towards lateral area gain during epitaxial growth. Yet promising, significant wafer area enhancement remained challenging. This work explores the growth dynamics of SCD in a constrained system, namely a pocket holder, whose effect is two fold: linear dimension and area enhancement and polycrystalline diamond (PCD) edge rim suppression. A series of pockettype holder designs were introduced that demonstrated that the depth and substrate-to-wall distance are the major means to optimize and enhance the lateral outgrowth while still suppressing the PCD rim. When taken together with reactor modeling, the pocket effect on the extent of ELO could be understood as directly manipulating and perturbing methyl radical flux near the growing diamond surface, thereby directly manipulating gas-to-solid phase transformation kinetics. Because it was further discovered that simple box-like pockets limit the ELO process to an exponential-decay scenario, a new generation of angled pockets was proposed that allowed to boost ELO to its fullest extent where a constant rate, linear, outgrowth was found. Our findings point out that ELO by MPACVD could mature toward becoming an industrial means to produce SCD at scale.